Consumer Acceptance of Central Bank Digital Currency in a Fully Launched Market - Golding, Paul (Technium Social Sciences Journal, 2024)
Since 2020 the number of countries and currency unions exploring the implementation of central bank digital currency (CBDC) has increased by approximately 300 percent. The literature shows an abundance of technical feasibility studies and a dearth of research on consumer adoption. This study investigates consumer adoption of CBDC in a market (Jamaica) in which it was already launched. Data was collected from 200 respondents based on a convenience sample. A conceptual model was constructed based on the unified theory of acceptance and use of technology. To validate the model and test the six hypotheses we employed PLS-SEM partial least squares structural equation modeling. Three of the six hypotheses were supported: behavioral intention has a significant positive impact on user behavior, social influence had a significant positive impact on behavioral intention, and facilitating conditions has a significant positive impact on user behavior. Age and gender had no moderating effect. This is the first study done in a market where CBDC was implemented, done on consumers and provided jurisdictional recommendation to create network effects and increase adoption